Principal Leadership Practices in the Early Stages of Covid-19 Pandemic Crisis - Dwi Esti Andriani; Ria Annisa; Baiquni Rahmat; Pandit Isbianti; Suyud Suyud; Slamet Lestari; Devi Monita Kristyningsih (Jurnal Manajemen Pendidikan : Jurnal Ilmiah Administrasi, Manajemen dan Kepemimpinan Pendidikan, 2021)
This study aimed to explore principal leadership at the beginning of the Covid-19 pandemic crisis. This study employed a qualitative approach that was exploratory and naturalistic with the purpose of gaining an understanding of a phenomenon in its natural setting. Data collection was carried out by semi-structured in-depth interviews with six elementary school principals who were selected purposefully using certain criteria. The collected data were then analyzed qualitatively using grounded theory methods. The member check technique was applied to assure data credibility. The results showed that principal leadership at the beginning of Covid-19 pandemic crisis was more concerned with achieving health for the school community than academic achievement. Therefore, they provided flexibility to teachers in managing instructions, created safe communication channels among all the school members, directly monitored and evaluated online learning, empowered competent teachers to develop the ICT skills of their colleagues, and fostered collaboration with stakeholders.